IMPLEMENTASI TOTAL QUALITY MANAGEMENT PADA KELAS INTERNASIONAL DAN AKSELERASI MTs. PPMI ASSALAAM SURAKARTA - Jasuri, Jasuri (Tadbir: Jurnal Manajemen Pendidikan Islam, 2014)
"The Implementation of Total Quality Management in International and Acceleration Classes of Junior Secondary Islamic Modern Boarding School (MTs PPMI) Assalaam Surakarta". This study is an effort to capture the application of Total Quality Management system in international and acceleration classes in MTs PPMI Assalaam Surakarta, including planning managers on TQM, the implementation of TQM, and TQM evaluation system. In this descriptive study, there are two sources of data, namely primary and secondary sources. The data were obtained through observation, interviews, and documentation. The results show the following three things. First, at the planning stage, the managers of the Education Services Program (PLP) MTs PPMI Assalaam for international and acceleration classes conduct coordination meetings in the framework of a program of action for these classes. In the meeting it was determined that the programs will be implemented during the year. This effort is intended that all matters related to the implementation of the program run systematic, focused, and according to the agenda. The effort is, for instance, to develop a work program in accordance with the inputs or students of international and accelerated classes.Second, the efforts of TQM application in the international and acceleration classes can be seen from: (1) the existence of problem solving between teachers, administrators, and students, (2) the provision of additional activities for students, such as AMT, tutoring, enrichment, drilling, and training that supports the interests and talents of students, (3) the exclusion of psychologists from both within (internal) or outside the cottage (external) to address the problems faced by students, and (4) engaging students in classroom management.Third, it is generally no disclosed term of evaluation for TQM implementation in international and acceleration classes MTs PPMI Assalaam. However, PLP managers especially still pursue the continuous assessment system in the form of learning evaluation and evaluation of planning programs.